Trends in technology-enhanced online learning for low achievers in introductory programming: a systematic literature review / Mahfudzah Othman ... [et al.] - Othman, Mahfudzah; Osman, Aznoora; Abdullah, Natrah; Ahmad, Siti Zulaiha (Universiti Teknologi MARA, Pulau Pinang, 2022)
Technology-enhanced online learning (TEL) has been widely utilized in facilitating teaching and learning in higher academic institutions. Although exhaustive studies have been done in investigating the usage and effectiveness of TEL in programming education, there are still insufficient studies on the utilization of TEL in introductory programming specifically for low achievers who often faced learning difficulties due to: the lack of motivation and interests, the lack of problem-solving skills and logical thinking and the technical issues in the technologies used. Therefore, this study investigates the trends of TEL in introductory programming in terms of its pedagogical approach in addressing the difficulties faced by the low achievers and the online technologies needed to facilitate their learning through a systematic literature review study from the year 2017 to 2021. By adopting Kitchenham’s methodology, a total of 20 papers were selected from various journals and databases. Researchers found that the trends of TEL for low achievers in introductory programming consisted of six main online educational technologies, which are the web-based learning, mobile learning, multimedia learning, gamification, block-based programming and virtual reality or robot simulations. The findings from this review can be used for future research in utilizing TEL in the field of programming education, especially for low achievers.